(untitled) (Research, Society and Development, 2021)
The coronavirus pandemic has extensively affected the most diverse stratums of society, especially the academic sector, causing a deficit in teaching, research and extension activities. Therefore, there was a need to develop and apply new tools, using Information and Knowledge Technologies (ICTs) and active methodologies, creating a path to the development of new skills and reconfiguring the teaching-learning process. Thus, this study is an experience report of the “Mind box” project as an example of an innovative tool that aims to promote teaching and university extension activities during the pandemic period incited by COVID-19. This project was active for six months and consisted of the production of a serie available in eight chapters that approached the neurosciences through themes of the theory of mind, consisting of a planning stage and an execution stage. The project had an approach based on active methodologies and ICTs in the new way to do extension. In this sense, the new information and communication technologies were used as innovative pedagogical tools, building scientific knowledge in a dynamic and interactive way. Hence, this model of project can be adopted for the dissemination of knowledge in other academic fields.